The effectiveness of Zhi-Shi plaster acupoint therapy combined with lactulose in the treatment of geriatrics functional constipation: a randomized controlled trial - Wang, Ying; Zhang, XiXia; Ding, XueFei; Li, Hui; Xia, JunQuan; Zhou, MengYan; Hua, YongZhi; Wu, KeXuan; Zhang, LongShu; Zhou, LiRong (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness and adverse effects of Zhi-Shi plaster acupoint therapy combined with Lactulose in the Treatment of geriatrics Functional Constipation.MethodsA total of 62 geriatrics Functional Constipation patients were randomly assigned to the intervention group (n = 31) and control group (n = 31). The intervention group received oral lactulose (20 mL daily for 14 consecutive days) plus Zhi-Shi plaster acupoint therapy (for 4 h daily at the following acupoints: CV8, bilateral ST25, and bilateral SP15). The control group received oral lactulose plus placebo acupoint therapy during the same period. The primary outcomes included the clinical efficacy and the Constipation Symptom Scoring Scale (CSS). Secondary outcomes included the weekly count of complete spontaneous bowel movements (CSBMs), the Bristol Stool Form Scale (BSFS), the Patient Assessment of Constipation-Symptoms (PAC-SYM), the Constipation Quality of Life Scale (PAC-QOL), and adverse effects. Assessments were conducted at baseline, the week1, the week2, and the week6, with data analysis using generalized estimating equations. And the outcome assessors and statistician was blinded.ResultsAfter treatment, the overall clinical efficacy was higher in the intervention group than in controls (96.77% vs. 83.87%, p = 0.03). The intervention group demonstrated superior improvements across outcomes compared to the control group: constipation symptoms (CSS: coefficient = −3.36, 95% CI: −4.68 to −2.03, p < 0.001), frequency of complete spontaneous bowel movements (CSBMs: coefficient = 0.59, 95% CI: 0.40 to 0.79, p < 0.001), and stool consistency (BSFS: coefficient = 0.45, 95% CI: 0.20 to 0.70, p < 0.001). Similarly, significant reductions in patient-assessed symptom severity (PAC-SYM: coefficient = −0.72, 95% CI: −0.91 to −0.52, p < 0.001) and greater enhancements in quality of life (PAC-QOL: coefficient = −0.34, 95% CI: −0.43 to −0.24, p < 0.001) were observed. Finally, the incidence of adverse reactions was lower in the intervention group (3.22% vs. 19.35%, p = 0.015).ConclusionThe combination of lactulose and Zhi-Shi plaster acupoint therapy for the treatment of geriatrics Functional constipation can significantly improve clinical efficacy, reduce adverse effects, alleviate symptoms and enhance quality of life.Clinical trial registryThis trial was registered in the International Traditional Medicine Clinical Trial Registry (ITMCTR; registration number: ITMCTR2024000401).